Estudos bioeletroquímicos de quinonas - Costa, Cícero de Oliveira (2011)
Many quinones have been associated with a wide range of biological activities, including antitumoral, antimalarial, larvicidal and antibacterial activities. Although, there are many clinically important agents containing a quinone nucleus with excellent anticancer activity, many other quinones require testing for additional activities, for instance: Oncocalyxone A, Juglone, Biflorin and some hydroxylated and halogenated quinones. DNA represents one of the main targets of biologically active quinonoid compounds, which, generally, belong to the group of DNA intercalating and/or alkylating agents, and/or topoisomerase inhibitors. As such, the use of DNA biosensors or other electrochemical methods based on the investigation of nucleic acid/organic compound interaction, would allow to predicting a biological action, if this one is related to damage to DNA. Due to the importance of quinones, for instance, Oncocalyxone A, Juglone and Biflorin, electrochemical analysis and the development of a new electroanalytical method for detection in nanomolar quantities, together with DNA interaction analysis with those quinones was therein performed. We have used diverse electrochemical methods performed in protic and aprotic media, using glassy carbon electrode, Ag/AgCl electrode as reference and latinum wire as counter electrode. The pKa of juglone was determined (5.98). The development of a highly sensitive voltammetric sensor for oncocalyxone A using a glassy carbon electrode modified with a bilayer iron(II) tetrasulfonated phthalocyanine (FeTSPc) and iron(III) tetra-(N-methyl-4-pyridyl)-porphyrin (FeT4MPyP) was described. The modified electrode showed catalytic activity and stability for the oncocalyxone A reduction, provoking the anodic shift of the reduction peak potentials of ca. 30 mV and presenting much higher peak currents than those obtained on the bare GC electrode. A wide linear response range between 0.005-1.210-6 mol L-1, with a sensitivity of 8.11 μA L μmol-1 and limits of detection (LOD) and quantification (LOQ) of 1.5 and 5.010-9 mol L-1 were obtained with this sensor, respectively. The interaction of chosen quinones with ssDNA, poly-guanilic and poly-adenilic acid was investigated, using voltammetric analysis, in solution. The DNA interaction investigation with juglone, oncocalyxone and biflorin had shown significant DNA activity, represented by the decrease of oxidation current and shift of oxidation peaks of guanine and adenine and the binding constant values obtained for these aducts; these observations could be related to Michael addition reaction, among other possible effects. Some of the quinones do not cause any change on the oxidation peaks of the used bases, as is the case of -lapachone, being used as negative control. These results, upon comparison with biological/ pharmacological activities, show correlation and indicate electrochemistry and DNA sensors as important tools in the screening of biologically active compounds.